Least Value

Algebra Level pending

Find for what value of parameter m m the sum of the squares of the roots of the equation x 2 + ( m 2 ) x ( m + 3 ) = 0 \large \color{#3D99F6}{x^{2}}+\color{magenta}{(m-2)x}-\color{#69047E}{(m+3)}=\color{#333333}{0} has the least value.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Md Zuhair
Mar 27, 2017

Simply we can say that,

the roots are α \alpha and β \beta .

So By Veita's Formula

α + β = 2 m \alpha + \beta = 2-m

α β = ( m + 3 ) \alpha \beta = -(m+3)

Solving for α 2 + β 2 \alpha ^2+ \beta ^2 we get

α 2 + β 2 = m 2 2 m + 1 \alpha ^2+ \beta ^2 = m^2-2m+1

Now this sum is minimum when

d ( α 2 + β 2 ) d m = 0 \dfrac{d(\alpha ^2+ \beta ^2)}{dm} = 0

So We get 2 m 2 = 0 2m-2 = 0

So m = 1 \boxed{m=1}

Tom Engelsman
May 10, 2020

Let the roots be A , B A, B and by Vieta's Formulae:

A + B = ( m 2 ) ( i ) , A B = ( m + 3 ) ( i i ) A+B = -(m-2) (i), AB = -(m+3) (ii)

Squaring (i) out produces A 2 + 2 A B + B 2 = ( m 2 ) 2 A 2 + B 2 = ( m 2 ) 2 2 ( m 3 ) = m 2 2 m + 10 = ( m 1 ) 2 + 9 ( i i i ) A^2 + 2AB + B^2 = (m-2)^2 \Rightarrow A^2 + B^2 = (m-2)^2 - 2(-m-3) = m^2 -2m + 10 = (m-1)^2 + 9 (iii)

Hence, (iii) is just a concave-up parabola that attains a global minimum value of 9 9 when m = 1 . \boxed{m=1}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...